Early ischemic CT changes before thrombolysis: The influence of age and diabetes mellitus - Lars Thomassen; Ulrike Waje-Andreassen; Halvor Naess (Dove Medical Press, 2008)
Lars Thomassen, Ulrike Waje-Andreassen, Halvor NaessDepartment of Neurology, Haukeland University Hospital, Bergen, NorwayObjectives: The significance of early ischemic changes (EIC) on computed tomography (CT) within 3 hours after stroke onset remains controversial. The semi-quantitative Alberta Stroke Program Early CT Score (ASPECTS) is found to have prognostic value in early stroke. This study assesses factors associated with the presence of EIC and the relation between EIC and clinical outcome.Materials and methods: CT scans from 61 consecutive patients receiving thrombolytic therapy were reviewed by 3 experienced stroke neurologists, assessing EIC (ASPECTS) and vascular signs (hyperdense middle cerebral artery stem and/or branches). Short-term outcome was assessed with the National Institute of Health Stroke Scale at 24 hours and long-term outcome with the modified Rankin Scale score after 3 months.Results: The prevalence of EIC was 54% and the agreement between assessors was good (kappa 0.52–0.67). EIC was independently associated with younger age and absence of diabetes mellitus. Neither EIC nor vascular signs were associated with 3-months outcome.Conclusions: ASPECTS is as simple, systematic approach to assessing EIC, and the interobserver agreement is good. Patient age and diabetes mellitus influence the presence of EIC.Keywords: acute stroke, computed tomography, ischemia, thrombolysis